PERANAN DANA BANTUAN SOSIAL TERHADAP KUALITAS RUMAH MASYARAKAT MISKIN MELALUI PROGRAM BEDAH RUMAH DI KABUPATEN BULELENG - Pramita, Asta Lugra; Yasa, I G W Murjana; Marhaeni, A.A.I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.02.TAHUN 2015, 2015)
Poverty is an issue that is important and fundamental to always be solved by every country in the world. Poverty causes a one not to meet his own basic needs and their families that encompasses physical, mental and social needs. To solve this problem the government is attempting to find solutions in various ways, one of which is through a social assistance (Bansos), a surgical program, managed by the Local Government. The aims of this study were 1) to analyze the perceptions of beneficiaries of house surgeon about the existence of this program, 2) to know whether there is an increase in the quality of the house of the poor community before and after receiving assistance of surgical program, 3) to determine what constraints faced by the Government in the implementation of surgical programs, 4) to determine the efforts made to overcome the shortcomings encountered in the surgical program in Buleleng. The data used were primary data and secondary data. Data collection methods used were observation, questionnaires, and in-depth interviews. The tool analysis used was descriptive and nonparametric statistical analysis using average paired difference test (Wilcoxon test). The results obtained were 1) the perception of poor beneficiaries of the existence of the house most of the surgical program provides a positive statement (Agree and Strongly Agree), the rest gave a statement neutral, and negative statements (Strongly Disagree and Disagree). 2) The Ho is rejected. This means that there is an increase in the quality of the house of the poor community after receiving surgical assistance. 3) The constraints faced in the implementation of the surgical program are verification, exploration, socialization, and development. 4) Efforts being made to overcome the disadvantages faced by the government in the implementation of the program are to prepare a consultant surgical assistant, handing the main actors in the home surgery program to the village community, and there is a need to develop standard conditions of prospective beneficiaries.
Keywords: surgical program, quality of the house, the poor, constraints